An unusual cause of systemic calcification-Fibrodysplasia Ossificans Progressiva - Sourya Sourabh Mohakuda; Rajneesh Thakur; Abdul Saleem (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2020)
Fibrodysplasia Ossificans Progressiva is a rare (incidence-one in two million people3) and disabling genetic condition, diagnosis of which is generally based on presence of congenital abnormality of great toes, progressive heterotopic ossification and the classical pattern of disease progression and radiological findings. Our case, a 29year old male presented with deformity of bilateral great toes since childhood, multiple hard swellings all over body leading to painful restriction of joint mobility and limitation of routine activities. Radiograph and bone scan revealed multiple sites of heterotopic ossifications.